The Influence of the Think-Pair-Share Cooperative Learning Model on Learning Outcomes on the Topic of Work and Simple Machines - Akuba, Siskawati; Odja, Abdul Haris; Buhungo, Trisnawaty Junus (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Science learning is often regarded as difficult by students due to the many concepts that are abstract and not well understood. Therefore, a learning model is required that can enhance students' academic performance. One of them is the cooperative learning model known as Think-Pair-Share (TPS), which encourages students to think independently, engage in paired discussions, and share ideas within their groups. This research aims to determine the effect of the Think-Pair-Share type cooperative learning model on the learning outcomes of simple machines and efforts in SMP Negeri 1 Kwandang. This study is an experimental research, utilising a one-group pretest-posttest Design. The sampling technique employed in this research is Cluster Random Sampling. The sample in this study uses class VIIIC as the experimental class, grouped through a random lottery. Data for this research were collected using a testing technique, which included normality tests, hypothesis tests, and n-gain tests. The analysis results indicate that the calculated values for all sample classes are greater than the tabulated values; thus, the hypothesis (H1) is accepted. The N-gain value of 0.80 indicates an improvement in learning outcomes that falls under the high category. The application of the Think-Pair-Share model, specifically for the material on simple machines and business, has rarely been researched before. This model has been proven to help students connect abstract concepts with real-life situations, fostering active participation in the learning process. Thus, the TPS type cooperative learning model has a significant impact on improving students' learning outcomes. This research also provides practical benefits as a basis for teachers to implement the cooperative model of Think Pair Share in learning to create a more active, effective, and meaningful learning atmosphere.